2011
DOI: 10.1093/rof/rfr030
|View full text |Cite
|
Sign up to set email alerts
|

Access to Liquidity and Corporate Investment in Europe during the Financial Crisis*

Abstract: Abstract. We use a unique data set to show how firms in Europe used credit lines during the financial crisis. We find that firms with restricted access to credit (small, private, non-investment-grade, and unprofitable) draw more funds from their credit lines during the crisis than their large, public, investment-grade, profitable counterparts. Interest spreads increased (especially in ''market-based economies''), but commitment fees remained unchanged. Our findings suggest that credit lines did not dry up duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
57
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(76 citation statements)
references
References 31 publications
14
57
2
Order By: Relevance
“…r = r + 1.5%, in a sample of 11,578 credit lines obtained by 4,011 public firms between 1996 and 2003. (Campello et al, 2012, report similar numbers in a recent survey of 800 CFOs from North America, Europe, and Asia.) For this value of the pre-committed interest rate, we have to raise the corporate tax rate to τ = 30% for the firm to use credit lines at all.…”
Section: E1(x;c * )supporting
confidence: 53%
“…r = r + 1.5%, in a sample of 11,578 credit lines obtained by 4,011 public firms between 1996 and 2003. (Campello et al, 2012, report similar numbers in a recent survey of 800 CFOs from North America, Europe, and Asia.) For this value of the pre-committed interest rate, we have to raise the corporate tax rate to τ = 30% for the firm to use credit lines at all.…”
Section: E1(x;c * )supporting
confidence: 53%
“…This is because the valuable cash tied up through working capital cycle contributes to business failures and played a critical role in firm performance during the financial crisis (Campello et al, 2011(Campello et al, , 2012Campello et al, 2010;Claessens et al, 2000;Pomerleano, 1998). It is then obvious to firms that their liquidity problems can only be solved through effective liquidity and cash management, since an effective way to lessen the reliance on external funding and counter-market difficulties is to continue to track and optimize internal resources (Rydel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Campello, E. Giambona, J. R. Graham and C. R. Harvey (2012) [8] reported that "the recent crisis did not severely hinder firms' ability to access lines of credit and draw down existing facilities". This proved to be of utmost importance for European companies as credit lines from banking sector became an essential way of financing and eased the financial crisis effect on investment and firm's financial performance, (as is shown Table 2).…”
Section: The Effect Of European Crisis On Investment Managementmentioning
confidence: 99%
“…Campello, Giambona, Graham, and Harvey (2012) [8] • examine how firms in Europe used credit lines during the financial crisis.…”
Section: The Effect Of European Crisis On Investment Managementmentioning
confidence: 99%